An Adolescent Presenting With Seizures as a Symptom of Gliomatosis Cerebri. Issue 12 (December 2018) - Blanco-Iglesias, Elena; Cabeza, Beatriz; Esparza, Elena Garcia; de Prada, Inmaculada; Lassaletta, Alvaro; Budke, Marcelo; Serrano, Ana
Abstract : Abstract: Gliomatosis cerebri is a diffuse infiltrating glioma of neuroepithelial origin that affects more than 2 cerebral lobes. This is rarely seen in pediatric patients. The clinical presentation and imaging are very unspecific, and a biopsy is typically needed for the diagnosis. Given the widespread nature of the disease, surgical treatment is not possible and has a poor overall prognosis. A pediatric patient presented with elevated intracranial pressure. All initial studies were negative, and the imaging showed a symmetrical affection involving the supratentorial and infratentorial regions. A biopsy ultimately confirmed gliomatosis cerebri. This case describes a unique clinical presentation of gliomatosis cerebri in a pediatric patient.